Modulation of resistance to anti-APO-1-induced apoptosis in osteosarcoma cells by cytokines - Fellenberg, Jörg; Mau, Hans; Scheuerpflug, Christian Gerold; Ewerbeck, Volker; Debatin, Klaus-Michael (International journal of cancer, 1997)
The CD95/APO-1/Fas receptor/ligand system plays a crucial role in growth control by mediating apoptosis in lymphoid and non-lymphoid cells. To investigate the role of CD95-mediated apoptosis in osteosarcoma, we studied 3 human osteosarcoma cell lines (HOS/TE 85, MG 63 and Saos-2) and osteoblasts derived from bone biopsies. In contrast to osteoblast-like cells, all cell lines were resistant to anti-APO-1-induced apoptosis despite constitutive CD95 expression at intermediate levels. Blocking of macromolecular synthesis by cycloheximide or actinomycin D or modulation of CD95 expression by cytokines (TNF-α and/or γ-interferon) restored sensitivity to anti-APO-1-induced cell death. PCR analysis of the CD95 transcripts revealed the production of a truncated splice variant that codes for a soluble form of the CD95 receptor. Synthesis and secretion of soluble CD95 protein into the culture supernatant was demonstrated by Western blot analysis. Treatment with sensitizing cytokines led to up-regulation of full-length CD95 transcripts and the encoded membrane-bound CD95 protein but not the truncated mRNA splice variant and the corresponding soluble receptor, as shown by PCR and Western blot analysis. The biological activity of soluble CD95 secreted by osteosarcoma cells was demonstrated by the ability of osteosarcoma supernatants to protect the sensitive T-cell line Jurkat from anti-APO-1-mediated apoptosis. Our results suggest that the production of soluble CD95 by osteosarcoma cell lines that may block physiological death signals and the production of membrane-bound CD95 are differently regulated by cytokines via modulation of RNA splicing. Int. J. Cancer 72:536-542, 1997. © 1997 Wiley-Liss, Inc.